Effect of sewage sludge fertilization in short‐rotation willow plantations - Lazdiņa, Dagnija; Lazdiņš, Andis; Kariņš, Zigurds; Kāposts, Visvaldis (Journal of Environmental Engineering and Landscape Management, 2007)
The aims of the research work were to evaluate increase of productivity of Salix energy crop and forest plantations by using sewage sludge fertilization, impact of sewage sludge on the environment, and to calculate economic income from plantations. The most important problem during the first rotation cycle in willow plantations was weed control. After using sludge weeds grew up, because sludge contains large amounts of nutrients. After cutting of sprouts in the second growth season willow plantations produce more sprout from stand, and productivity increases from 0,2–0,6 t to 4,6–5,5 t of dry mass/ha. Effect of sewage sludge fertilization is greater in the second season both in control plantations and fertilized plantations. Average biomass production in fertilized plantations was 5,5 t of dry mass/ha per year. Shoot wood from fertilized plantations contained on the average by 4–8 % more heavy metals than control plantation wood. The concentration of heavy metals in the top soil layer increased, but it did not exceed the Regulations issued by the Cabinet of Ministers of Latvia about the soil quality, and the soil cultivation in the first three years was 760 LVL/ha. If the distance were not longer than 40 km and a willow‐cutting combine operated without pauses, costs for cutting, chip crushing and delivery to consumers would achieve 4 LVL/m3. Tręšimo nuotekų dumblu įtaka trumpos rotacijos karklų plantacijoms Santrauka. Mokslinio tiriamojo darbo tikslai yra įvertinti miško prieaugį ir Salix energinį pasėlių produktyvumą tręšimui naudojant nuotekų dumblą; nuotekų dumblo įtaką aplinkai ir apskaičiuoti plantacijų ekonominę naudą. Svarbiausia problema pirmosios rotacijos karklų plantacijose buvo piktžolės. Dumblą paskleidus piktžolės augo, nes jame buvo daug nitratų. Antrojo karklų augimo sezono metu jie duoda daugiau atžalų, todėl produktyvumas padidėjo nuo 0,2–0,6 t iki 4,6–5,5 t sausosios masės iš hektaro. Tręšimo nuotekų dumblu įtaka buvo didesnė kontrolinėse ir tręštose plantacijose antrojo augimo sezono metu. Vidutinis biomasės kiekis tręštose plantacijose buvo 5,5 t sausosios masės į hektarą per metus. Ūglių medienoje tręštose plantacijose buvo vidutiniškai 4–8 % daugiau sunkiųjų metalų nei kontrolinių plantacijų karklų medienoje. Sunkiųjų metalų koncentracija paviršiniame dirvožemio sluoksnyje padidėjo, bet neviršijo Latvijos ministrų kabineto nustatytų leidžiamųjų dirvožemio kokybės ribų, dirvožemio rekultivacija per pirmuosius trejus metus buvo 730 LVL/ha. Jei atstumas neviršytų 40 km ir karklų pjovimo kombainas dirbtų be pertraukų, pjovimo, smulkinimo ir pristatymo vartotojams išlaidos siektų 4 LVL/m3. Reikšminiai žodžiai: karklai, plantacijos, mediena energijai, nuotekų dumblas, tręšimas. Влияние илового удобрения на плантации ивняка короткой ротации Резюме. Целью научного исследования было оценить прирост леса и энергетическую продуктивность посевов Salix в результате использования в качестве удобрения сточного ила; воздействие, оказываемое сточным илом на окружающую среду, и рассчитать экономическую пользу плантаций. Главной проблемой на плантациях ивняка первой ротации были сорняки. После попадания ила на плантации быстро росли сорняки из-за большого количества нитратов в нем. Во время второго сезона роста ивняка появлялось много отростков, продуктивность увеличивалась от 0,2–0,6 т до 4–5,5 т сухой массы с гектара. Влияние илового удобрения было большим на контрольных и удобренных плантациях во время второго сезона роста. Среднее количество биомассы на удобренных плантациях составило 5,5 т сухой массы за год. В ростках древесины с удобренных плантаций в среднем было на 4–8 % больше тяжелых металлов, чем в древесине ивняка с контрольных плантаций. Концентрация тяжелых металлов в поверхностном слое почвы увеличилась, хотя и не превысила установленных Правительством Латвии предельных величин. Рекультивация почвы в первые три года составила 730 латов/га. В случае, если расстояние не превышает 40 км и комбайн по срезке ивняка работает без перерывов, расходы на срезку, измельчение и доставку потребителям составят 4 лата/м3. Ключевые слова: ивняк, плантации, древесина, сточный ил, удобрение. First Published Online: 14 Oct 2010